Discovery of Small Molecule WWP2 Ubiquitin Ligase Inhibitors. Issue 67 (6th November 2018) - Watt, Jessica E.; Hughes, Gregory R.; Walpole, Samuel; Monaco, Serena; Stephenson, G. Richard; Bulman Page, Philip C.; Hemmings, Andrew M.; Angulo, Jesus; Chantry, Andrew
Abstract: We have screened small molecule libraries specifically for inhibitors that target WWP2, an E3 ubiquitin ligase associated with tumour outgrowth and spread. Selected hits demonstrated dose‐dependent WWP2 inhibition, low micromolar IC50 values, and inhibition of PTEN substrate‐specific ubiquitination. Binding to WWP2 was confirmed by ligand‐based NMR spectroscopy. Furthermore, we used a combination of STD NMR, the recently developed DEEP‐STD NMR approach, and docking calculations, to propose for the first time an NMR‐validated 3D molecular model of a WWP2‐inhibitor complex. These first generation WWP2 inhibitors provide a molecular framework for informing organic synthetic approaches to improve activity and selectivity. Abstract : HTS screen and DEEP‐STD NMR validation of a 3D structural model was used to discover a new class of WWP2 ubiquitin ligase inhibitors.